Model Picture and Picture untuk Meningkatkan Keterampilan Berbicara Sesuai Unggah-ungguh - Bethy Mahara Setyawati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2021)
The aim of this research is to improve students’ activeness and learning outcome based on Javanese etiquette in Class VIIIB of SMP Negeri 4 Wates. This research is carried out in two cycles, each consisting of planning, action, observation and reflection. The subject of this research is students of Class VIIIB in SMP Negeri 4 Wates, 31 students. The data collection technique uses observation, notes and speaking test based on Javanese etiquette. The research outcome shows students’ activeness improves than before they were given action, cycle 1 and cycle 2. The learning outcome in cycle 1 shows there are 2 students (6%) in very skilled category, 9 students (29%) in skilled category, 7 students (23%) in medium skilled category and 13 students (42%) in less skilled category. In cycle 2, there are 8 students (26%) in very skilled category, 11 students (32%) in skilled category, 2 students (11%) in medium skilled category and 4 students (20%) in less skilled category.